PERMODELAN SISTEM INFORMASI GEOGRAFIS (SIG) DALAM ANALISIS DISTRIBUSI RUANG DEBIT BANJIR (SPATIAL DISTRIBUTION OF FLOOD) SUNGAI BERINGIN - Pranoto Samto Atmojo; Priyo Nugroho Parmantoro; Dyah Ari Wulandari; Suharyanto Suharyanto (KEAIRAN, 2001)
The significant and un-controlled land use change in Bringin River has affected the downstream area i.e.,increased  flooding intensity and frequency. This condition is becoming worse with the increase number developer opening the area at the upstream area. Therefore, the impact of the downstream flooding should also be the responsibility of those developers. This paper focused on the evalution of spatial distribution of the river discharge over the Bringin River’s catchment area, which therefore able to give some indication on the responsibility proportion on floodings. The paper demonstrate the use of GIS to model the spatial distribution of floods over the catchment area. This paper show that there’s 6.39 % increase in 2002 floodings. In general, the total proportion of the overall developer in less than 15 % compared to the “contribution of traditional housing of about more than 25 %.